PERFORMANCE-BASED ASSESSMENT IN THE ENGLISH LEARNING PROCESS: WASHBACK AND BARRIERS - Nila Salma; Entika Fani Prastikawati (English Education Department, 2021)
In the context of assessment, performance-based assessment is one of the authentic assessments to be applied in the English classroom as the completion of the newest curriculum demands. Thus, teachers are suggested to implement this assessment in the English teaching and learning process. Concerning that fact, this current study aims at investigating the washback of the use of performance-based assessment in the English class and the barriers faced by the teachers in implementing performance-based assessment in the English learning process. This study applied a qualitative research design. Using purposive sampling, there were two teachers and 72 students who participated in this study. An open-ended questionnaire and semi-structured interview were carried out in collecting the data. The result showed that performance-based assessment affected positively to the teachers. They could identify the students’ real competence, improve their teaching quality, and assess students objectively. Further, it gives positive effects for the EFL learners in matters such as learning enthusiasm and self-confidence, boredom reduction, and skill improvement. In conclusion, the use of performance-based assessment is good at improving some teaching aspects both on teachers and students. This findings prove the importance of performance-based assessment to bost the teaching and learning quality.